Teaching Java Programming using CABLE in a Collaborative Online Environment - Nigel McKelvey; Kevin Curran (International Journal of Evaluation and Research in Education (IJERE), 2012)
With the emergence and evolution of computer hardware, software and networks - virtual classrooms now exist which enable teachers and students to experience learning activities and to work together at a distance either directly or on a part-time basis. We are increasingly confronted with a need for ‘lifelong training’ and it is becoming increasingly difficult for us to attend physical classrooms on a full-time basis. Research to date has highlighted an area of interest with regard to teaching computer programming in an online environment. We investigate here the use of a Cognitive Apprenticeship-Based Learning Environment (CABLE) in the teaching of Java programming in an attempt to validate its effectiveness. This paper outlines the result of using a pedagogical model which employed a combination of instructional strategies including directive support, responsive cognitive apprenticeship, collaborative learning, stimulating metacognition (organising, motivating (through a “spark”, modifying one’s own skills), and using various technologies via the use of online discussion through Blackboard.DOI: http://dx.doi.org/10.11591/ijere.v1i1.521